The double-edged impact of Internet use on mental health outcomes among Filipino university students: the mediating role of online social support - Abad Santos, Paolo Miguel T.; Cleofas, Jerome V.; Austria, Arianne Gail O.; de Guzman, Alejandra Kamiya B.; Sarile, Brianna Angela F. (Frontiers in Sociology, 2023)
Introduction Evidence supports both the positive and negative effects of Internet use on mental health outcomes, but it remains unclear on the role of online social support in this relationship. This study examined the link between daily hours of general Internet use and bidimensional mental health (BMMH) through the pathway of online social support (OSSS). Methods Drawing from a sample of 247 Filipino university students, this cross-sectional study tested two simple mediation models that considered mental wellbeing and psychological distress as outcome variables. Results Findings show that the total effect of Internet use is positive and negative for mental wellbeing and psychological distress, respectively. Online social support mediated the favorable effects of Internet use on BMMH outcomes. However, the introduction of OSSS as a mediator yielded residual direct effects with opposing signs for both models. The resultant inconsistent mediation in the models signifies the double-edged impact of Internet use on mental health, with favorable effects transmitted through online social support. Discussion Findings highlight the importance of online social support as a pathway to harness the positive effects of Internet on mental health. Recommendations to improve online social support for students are discussed herein.